Bilateral Sclerosing Stromal Ovarian Tumor in an Adolescent - Anjani Naidu; Betty Chung; Mitchell Simon; Ian Marshall (Case Reports in Radiology)
Sclerosing stromal tumor of the ovary is a rare, benign, sex cord stromal tumor occurring predominantly in younger women in the 2nd and 3rd decades of life. It typically presents unilaterally with only 2 previously reported cases of bilateral presentation. Common clinical presentations include pelvic or abdominal pain, a mass, or menstrual changes. Although occasionally presenting with hormonal manifestations, virilization as a result of androgen production by the tumor is rare. Here we present an extremely rare case of a sclerosing stromal ovarian tumor in a 14-year-old patient with bilateral presentation and with clinical and biochemical evidence of hyperandrogenemia.